The impact of brain-derived neurotrophic factor gene polymorphisms on post-stroke naming in aphasia - Randighieri, Matilda; Devine, Alyssa; Kelly, Lindsey; Tilton-Bolowsky, Victoria; Neal, Voss; Kang, Joseph; Bösel, Julian; Hillis, Argye Elizabeth; Stockbridge, Melissa D. (PLOS ONE, 2025)
Post-stroke aphasia, or language deficits after stroke, afflicts 20-30% of survivors and often persists into the chronic phase. The protein brain-derived neurotrophic factor has been identified as important for neuroplasticity, and is regulated by the brain-derived neurotrophic factor gene. A patient’s brain-derived neurotrophic factor genotype may influence their post-stroke aphasia recovery. This study aimed to investigate the impact of a single nucleotide polymorphism in the brain-derived neurotrophic factor gene, rs6265, on language recovery. We hypothesized that individuals with the most common polymorphism would exhibit better chronic naming performance and a more favorable recovery trajectory from poor acute performance to strong chronic outcomes compared to those without the polymorphism. We retrospectively analyzed data from 77 participants with post-stroke aphasia from three recent or ongoing studies that included both repeated standardized picture naming assessments in the acute, subacute, and chronic phases and brain-derived neurotrophic factor genotyping. Statistical analyses controlled for acute performance and lesion volume when evaluating the effect of brain-derived neurotrophic factor genotype on the probability of better chronic language recovery (Aim 1) and on the probability of a person with poor acute performance later having strong performance in the subacute to chronic period (Aim 2). Results indicated that those with the most common polymorphism had a 33% higher likelihood of high naming scores in the chronic phase compared to those with the with less common polymorphisms (with a methionine allele). Individuals with the typical polymorphism whose acute naming was below average after stroke exhibited a 24% higher likelihood of recovering to be above average. Brain-derived neurotrophic factor status was not a significant independent predictor of outcome in either model. Our results suggest that the effect of brain-derived neurotrophic factor polymorphisms on chronic post-stroke aphasia recovery is, at best, modest and underscores the importance of individualized approaches to neurorehabilitation.